2021
DOI: 10.1111/jcmm.16787
|View full text |Cite|
|
Sign up to set email alerts
|

ADMSC Exo‐MicroRNA‐22 improve neurological function and neuroinflammation in mice with Alzheimer's disease

Abstract: The previous study by our group has found that miRNA‐22 can inhibit pyroptosis by targeting GSDMD and improve the memory and motor ability of mice with Alzheimer's disease (AD) mice by inhibiting inflammatory response. In recent years, stem cells and their exosomes have been reported to have good therapeutic effects on AD; therefore, we hypothesize that miRNA‐22 is likely to play a synergistic therapeutic effect. In this study, adipose‐derived mesenchymal stem cells (ADMSCs) were transfected into miRNA‐22 mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…Also, miR-29 enriched MSC-derived exosome therapy resulted in decreased pathological impacts of Aβ peptide in a rodent model of AD and then improved spatial learning and memory [ 143 ]. On the other hand, miRNA-22-loaded AT-MSC-derived exosomes enhanced the motor and memory capability of mice model of AD by improving neural survival in vivo [ 144 ]. In vitro analysis also suggested that improved neural survival relies on the inhibition of inflammatory factors secretion and downregulation of the pyroptosis process, which was provoked by exosomal miRNA-22 [ 144 ].…”
Section: Preclinical Studies Based On Msc-derived Exosome Therapy In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, miR-29 enriched MSC-derived exosome therapy resulted in decreased pathological impacts of Aβ peptide in a rodent model of AD and then improved spatial learning and memory [ 143 ]. On the other hand, miRNA-22-loaded AT-MSC-derived exosomes enhanced the motor and memory capability of mice model of AD by improving neural survival in vivo [ 144 ]. In vitro analysis also suggested that improved neural survival relies on the inhibition of inflammatory factors secretion and downregulation of the pyroptosis process, which was provoked by exosomal miRNA-22 [ 144 ].…”
Section: Preclinical Studies Based On Msc-derived Exosome Therapy In ...mentioning
confidence: 99%
“…On the other hand, miRNA-22-loaded AT-MSC-derived exosomes enhanced the motor and memory capability of mice model of AD by improving neural survival in vivo [ 144 ]. In vitro analysis also suggested that improved neural survival relies on the inhibition of inflammatory factors secretion and downregulation of the pyroptosis process, which was provoked by exosomal miRNA-22 [ 144 ].…”
Section: Preclinical Studies Based On Msc-derived Exosome Therapy In ...mentioning
confidence: 99%
“…The miR-125a found in BM-MSCs promotes M2 macrophage polarization, which was attenuated by the knockdown of this miRNA (Chang et al, 2021 ). Transfection of AT-MSCs with miR-22 mimics resulted in a mir-22 enriched pool of Evs and reduced inflammation in a mouse model of AD (Zhai et al, 2021 ). Also, Evs of MSCs transfected with miR-26a-5p and miR-221-3p mimic, respectively, attenuated ischemia/reperfusion injury and stroke (Ai et al, 2021 ; Cheng et al, 2021 ).…”
Section: Msc-derived Exosomes and Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In a mouse model of Alzheimer’s disease induced by LPS, miR-146a was enriched in EVs under inflammatory conditions, and EVs can induce inflammation and LPS tolerance [ 79 ]. Using the APP/PS1 mouse model of Alzheimer’s disease, miR-22 in exosomes from ADMSC enhanced neurological function, inhibited PC12 apoptosis, and decreased inflammatory factors by inhibiting proptosis [ 80 ].…”
Section: Main Textmentioning
confidence: 99%